A preliminary study of vehicular traffic distribution in Great Mendoza area: use of IoT tools - Marianetti, Osvaldo (2023)
This paper discusses the use of Radar Sensor Network at Great Mendoza area in order to register and to store vehicular traffic information. Both the network features and the software used in order to analyze and post process the captured information are provided. The main issues of vehicular traffic flow at Great Mendoza area are described from a qualitative point of view. Preliminary results registered with a Radar Sensor Networks placed at Godoy Guaymallén department are discussed as well. Based on the obtained results it can be expected that this kind of tools be very useful in order to alleviate vehicular traffic bottlenecks and related problems.